Dietary carbohydrate requirements for muscle glycogen resynthesis following exercise - Florin, T. D.; Damian, P. (Science, Movement & Health, 2026)
Aim. The aim of this research is to investigate the physiological mechanisms and time course of muscle glycogen resynthesis over a 24- hour recovery period following endurance exercise. Methods. We searched the following computerized databases: Web of Knowledge, Google Scholar and profile websites to collect recent data on the influence of recovery in elite sport. A comprehensive review of nutritional protocols was conducted, focusing on the physiological transition between insulin-independent and insulin-dependent phases of glycogenogenesis. The analysis incorporated contemporary intake thresholds (100-120 g/h) and mass-based saccharide proportions (1:0.8 glucose-to-fructose ratio). Results. The findings demonstrate a significant temporal advantage in glycogen loading when carbohydrates are administered within the immediate 30-minute post-exercise window. Delaying intake by two hours results in a 50% reduction in synthesis rates. Conclusions. The initial 30-minute post-exercise window, characterized by an insulin-independent phase, represents the most physiologically efficient period for metabolic restoration. Specifically, the restoration of muscle glycogen after exercise can be achieved by ingesting approximately 60 g of carbohydrates per hour during the first 2-3 hours (Rollo, 2014). To optimize metabolic recovery in elite athletes, the utilization of multiple transportable carbohydrates—specifically a 1:0.8 glucose-to-fructose blend—is essential to circumvent the 60 g/h absorption bottleneck. This nutritional framework supports high-intensity energy demands by maximizing total carbohydrate flux and enhancing systemic glycogen resynthesis while maintaining superior gastrointestinal tolerance. The co-ingestion of glucose (for intramuscular glycogen) and fructose (for hepatic glycogen) is superior to separate administration, and high-glycemic index carbohydrates are vital for stimulating insulin and maximizing muscular glycogen accumulation.